Design and implementation of the visual davinci language - Champredonde, Raúl (1997)
A visual language, called Visual DaVinci is presented in this article, along with its implementation most important aspects. Visual DaVinci was specially developed for structured programming initial teaching at computer sciences courses of studies. It uses the control flow paradigm by specifying diagrams similar to the Nassi-Schneiderman one, thus forcing the development of a structured code. Diagrams are automatically derived to textual code, which can be modified by the programmer. It also allows a textual development of the code, with a restricted syntax that also requires the generation of a structured code and the keeping of certain rules regarding programming style. Syntactic verification and execution are based on the code, in order to free language efficiency from its visual nature.